Pengaruh Penyulangan Medium yang Mengandung Orange II terhadap Pertumbuhan Enterococcus faecalis ID 6017 dan Kemampuan Dekolorisasinya - Meitiniarti, V. I.; Sunardi, E. Vandiyani; Timotius, K. H. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
The influence of fed Orange II containing medium on the growth of Enterococcus faecalis ID 6017 and its decolorization ability was studied in this research. A fed batch growth was compared with the batch growth. Total Orange II added to the both was 120 mg/L. In the fed batch, the Orange II was given into three steps. The first addition was at the initial culture medium. The second and third were added after the almost total decolorization or clearance of the Orange II given in the first or the second addition respectively. The culture was incubated under static condition and room temperature. The fed batch growth was better than the batch growth, seen from both aspects; their growth parameters and the decolorization ability. The biomass yield and specific growth rates of the fed batch was higher than the batch growth. Under fed batch growth, the decolorization was 85-94%, while the batch growth was only 54%. For achieving these performances, the fed batch growth was needed to consume more glucose.